2011
DOI: 10.1111/j.1523-536x.2011.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Movement Counting-Effects on Maternal-Fetal Attachment: A Multicenter Randomized Controlled Trial

Abstract: Fetal movement counting in the third trimester does not stimulate antenatal maternal-fetal attachment. This result differs from a previous study where fetal movement counting improved maternal-fetal attachment. Further research with a focus on possible mediating factors such as levels of stress, concern, and other psychological factors is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
1
42
2
Order By: Relevance
“…Earlier studies have suggested that maternal-fetal attachment develops especially after quickening of the fetus [22], and that a mother’s sensitive perception of fetal movements contributes to enhancing attachment to the fetus [15-18], though a recent study did not show the effectiveness of fetal movement counting on attachment [29]. It can be easier to sense fetal movement through the abdominal wall than with the central nervous system [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have suggested that maternal-fetal attachment develops especially after quickening of the fetus [22], and that a mother’s sensitive perception of fetal movements contributes to enhancing attachment to the fetus [15-18], though a recent study did not show the effectiveness of fetal movement counting on attachment [29]. It can be easier to sense fetal movement through the abdominal wall than with the central nervous system [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that the women who counted the fetal movements in the third trimester reported to have fewer concerns than the control group (Saastad, Winje, Israel, & Froen, 2012). Another study reported that the fetal movement counting does not affect on maternal fetal attachment (Saastad, Israel, Ahlborg, Gunnes, & Froen, 2011). However, contradictory findings have been reported about the impact of fetal movement counting on maternal fetal attachment, but so far the impact of fetal movement counting on general health of mother has not been studied.…”
Section: Theoretical Framework and Literaturementioning
confidence: 92%
“…Two studies on fetal movement counts and maternalfetal attachment showed opposite results. The first study showed that women who counted fetal movements at the late gestational stage did not have enhanced levels of maternal-fetal attachment, comparedwithwomen who received standard prenatal care [41]. By contrast, the second study found that 1month of fetal movement counting increasedthe level of maternal-fetal attachment [42].…”
Section: Related Intervention Studies On Maternal-fetal Attachmentmentioning
confidence: 99%